Immune modules shared by innate lymphoid cells and T cells - Robinette, Michelle L.; Colonna, Marco (Journal of allergy and clinical immunology, 2016)
In recent years, innate lymphoid cells (ILCs) have emerged as innate correlates to T cells. The similarities between ILCs and T cells indicate that lymphocytes of fundamentally distinct lineages can share core “immune modules” that encompass transcriptional circuitry and effector functions while using nonredundant complementary mechanisms of pattern recognition to enact these functions. We review modules currently recognized to be shared between ILCs and T cells.